Ergonomics in Caring for People Proceedings of the International Conference on Humanizing Work and Work Environment 2015 - Ray, Gaur G.; Iqbal, Rauf.; Ganguli, Anindya K.; Khanzode, Vivek; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This volume comprises the proceedings of the International Conference on Humanizing Work and Work Environment organized by the Indian Society of Ergonomics. The book presents research findings on different areas of ergonomics for developing appropriate tools and work environment considering capabilities and limitations of working people for maximum effectiveness on their performance. The volume is divided into several sections focusing on different ergonomic research activities currently being undertaken at both national and international levels. Considering the high diversity among researchers contributing to this volume, it should prove to be a valuable collection of different approaches that contemporary researchers are adopting on the theme of caring for the people and humanizing work and work environment.  .
PART I: Biomechanics.- Chapter 1: Impact of Footwear on Gait Pattern -- Chapter 2: Characteristics of Gait Variability Among Healthy Indian Construction Workers during Different Load Carrying Modes.- PART II: Musculo Skeletal Disorders.- Chapter 3: A Study on Agony of Indian Percussionists -- Chapter 4: Prevalence of Upper-Limb Disorders and investigation of Risk Factors Among Commercial Kitchen Male Workers in South India -- Chapter 5: Effect of Occupational Factors on Musculoskeletal Disorders of the insurance office Employees: A Case Study -- Chapter 6: Assessment of forearm Muscle Work in Various Dental Activities -- Chapter 7: Investigation of Magnitude of Musculoskeletal Disorders Among Cotton Spinning Operators -- Chapter 8: Working Period, Year of Exposure and the Prevalence of Musculoskeletal Disorders Among the Saw Mill Workers: A Cross Sectional Study -- Chapter 9: Duration of Exposure (Working Hours) and Musculoskeletal Discomfort/Pain.- PART III: Health & Safety.- Chapter 10: Knowledge-Attitude-Practice (Kap) Study and Nutrition Education of Athletic and Non-Athletic Teenagers (13-18 Years) -- Chapter 11: A Study on Auditory Status of School Going Children Residing Near Railway Track -- Chapter 12: Assessment of Scapular Stability in Postpartum Females -A Longitudinal Study -- Chapter 13: General Health Related Physical Fitness Levels of College Going Girls from Maharashtra -- Chapter 14: Bagasse -A Replacement of Glass Wool as an Acoustic Material.- PART IV: Occupational Ergonomics.- Chapter 15: Manual Material Handling by Rural Women: An in-depth Analysis of the Body Pain Areas -- Chapter 16: Characterization of Drudgery of Farm Women in the Soybean Production System -- Chapter 17: Association of Job and Demographical Risk Factors with Occurrence of Neck Pain Among Hand Screen PrInting Workers -- Chapter 18: Effect of Fatigue on Hand Function in Dental Profession -- Chapter 19: Cardiac Stress Among Two Types of Handloom Weavers -- Chapter 20: Workspace Amenities for Assam Policewomen: Ergonomic Interventions -- Chapter 21: Physiological and Metabolic Status of Bus Drivers -- Chapter 22: Effectiveness of a Participatory Ergonomics Intervention to Improve Musculoskeletal Health: A Solomon Four-Group Study Among Manufacturing Industry Workers in Selangor, Malaysia.- PART V: Design Ergonomics.- Chapter 23: Ergonomic Intervention for Manual Harvesting in Agriculture: A Review -- Chapter 24: Skin-Bed Interface Pressure on Standard Hospital Mattress for Sitting, Prone and Supine Posture in Healthy Adults -- Chapter 25: Designing a Continuously Variable Transmission Mechanism for Economy Cars in India -- Chapter 26: A Brief Procedure for Ergonomic Design of Hand tool for Small Scale Industries -- Chapter 27: Designing Washroom for Wheelchair Users in Vocational Training Schools -- Chapter 28: Intra and Inter Reliability of Cervical Goniometer Used to Measure Cervical Range of Motion in Young Adults.- PART VI: User Experience.- Chapter 29: Number Plate Design for Bicycles: An Approach from Aesthetic and Ergonomic Perspective -- Chapter 30: Anthropomorphic Televisions are more Attractive: The Effect of Novelty -- Chapter 31: Identification of Aesthetically Favorable Interface Attributes for Better User Experience of Social Networking Application -- Chapter 32: Exploring Embedded Intelligence as a means of Minimizing Cognitive Load of Students in Electronics Engineering Instructional Laboratory Sessions -- Chapter 33: Product User Interfaces: A Study for the Meaning and Usability of Graphical User Interfaces in Indian Context -- Chapter 34: Effect of Baby-Like Product Personality on Visually Perceived Pleasure: A Case Study on Coffee Makers -- Chapter 35: Quantitative Probabilistic Widgets' as a method to improve Usability Performance of Data Entry Tasks.- PART VII: Cognitive Ergonomics.- Chapter 36: An Eye-Free Android Application for Visually Impaired Users -- Chapter 37: Meditation as a Countermeasure to Reduce Cognitive Decline during total Sleep Deprivation -- Chapter 38: Effects of Bharatnatyam Dancing on the Cognitive Ability of Adult Bengalee Females -- Chapter 39: A Cognitive Approach to Design of Habitats in Extraterrestrial Environments: Review of Literature -- Chapter 40: Mental Fatigue Quantification by Physiological and Neurophysiological Techniques: An Overview -- Chapter 41: Role of Language in Transfer of Tacit Knowledge: Case Study of Bamboo Crafts Making industries in North East India -- Chapter 42: Study of Visual Ergonomic Issues in Title Design in Popular Hindi Cinema Posters -- Chapter 43: Research in Driver-Vehicle Interaction: Indian Scenario.
Keywords: Security systems; Engineering design; Employee health promotion; Occupational health services; User interfaces (Computer systems).; Human-computer interaction; Human physiology; Security Science and Technology; Engineering Design; Employee Health and Wellbeing; Occupational Health; User Interfaces and Human Computer Interaction; Human Physiology